Implementasi Fiqih Ibadah dalam Pelaksanaan Puasa Ramadhan di Era Modern - Balillah, Alifa; Tawakal, Kukuh Bina; Nurdin, Amrullah; Syamsiah, Syamsiah; Armansyah, Yudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to examine the implementation of Islamic law of worship in the implementation of Ramadan fasting in the modern era, by highlighting the challenges and adaptations of Muslims in carrying out fasting according to the guidance of sharia amidst the development of the times. The method used is qualitative descriptive with limited field observation. The results of the study indicate that although the basic principles of Islamic law of fasting remain relevant, there are various dynamics in its practice, such as the use of technology in determining the beginning of Ramadan and Eid al-Fitr, fasting time management amidst modern busyness, and attitudes towards health conditions and heavy work. In the digital era, the role of social media and online preaching platforms also have a major influence on the understanding and practice of fasting worship. This study concludes that the fiqh of worship has high flexibility in responding to changes in the times, as long as it adheres to established sharia principles. Thus, a contextual understanding of fiqh is very important to maintain the essence and solemnity of fasting worship amidst the challenges of the modern era.